NAVIGATING INTERNATIONAL ACCOUNTING ISSUES IN A GLOBALIZED ECONOMY: https://doi.org/10.5281/zenodo.15493479 - Odilov, Qudratulla (Journal of Contemporary World Studies, 2025)
This article analyzes the key international accounting challenges faced by businesses and regulators in an increasingly globalized economy. With the expansion of cross-border transactions, multinational corporations encounter differences in accounting standards, reporting requirements, and tax regulations. The study emphasizes the role of International Financial Reporting Standards (IFRS) in harmonizing global accounting practices and explores the impact of cultural, legal, and institutional differences on financial transparency and comparability. Through comparative analysis and case studies, the article highlights the need for improved international cooperation, capacity-building, and adoption of digital tools to ensure accuracy and consistency in global financial reporting.